A note on nontrivial intersection for selfmaps of complex Grassmann manifolds - Monis, Tháis F.M. [UNESP]; Penteado, Northon C.L. [UNESP]; Ura, Sergio T. [UNESP]; Wong, Peter (Belgian Mathematical Soc Triomphe, 2017)
Let G(k,n) be the complex Grassmann manifold of k-planes in Ck+n. In this note, we show that for 1 < k < n and for any selfmap f: G(k,n) → G(k,n), there exists a k-plane Vk ∈ G(k,n) such that f(Vk) ∩ Vk ≠ {0}.
Keywords: fixed points; complex Grassmann manifolds